Literature Study of Hindu Religious Life In The Reform Era - Surpa, Wayan; Dwi Wismayanti, Kadek Wiwin (Green Publisher Indonesia, 2023)
The rapid development of the times accompanied by the currents of globalization has caused a process of change in culture in Indonesia. One of the changes felt by the community is the change in Hindu religious life. The changes that occurred in Hindu religious life along with the development and pace of globalization caused a cultural shift. This cultural shift certainly has an influence on the pattern of Hindu life in people's lives. Cultural shifts in Hindu religious life such as dress codes, lack of participation of the younger generation in religious activities such as ngayah, furniture, mekidung and the fading of traditions that develop in society. In addition, the changes that have occurred in Hindu religious life have occurred due to the development of tourism. This is due to technological advances that make it easier for people to make Bali a cultural-based world tourist destination. Currently, the existing cultural system is packaged by keeping up with the times. The purpose of this study is to find out how the development of Hindu religious life in the revolutionary era. This research method uses a literature review approach